2020
DOI: 10.1111/den.13891
|View full text |Cite
|
Sign up to set email alerts
|

Case of descending colon schwannoma diagnosed by endoscopic ultrasound guided fine needle aspiration using an overtube

Abstract: https://onlinelibrary.wiley.com/pages/journal/14431661/den13891-sup-0001-vidS1.htm a video of this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Akahoshi et al used the single-cannula-assisted technique mentioned above for the fine-needle aspiration of a descending colon schwannoma [ 4 ]. Trikudanathan et al reported a case of a schwannoma at the splenic flexure of the colon [ 30 ].…”
Section: Clinical Applicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Akahoshi et al used the single-cannula-assisted technique mentioned above for the fine-needle aspiration of a descending colon schwannoma [ 4 ]. Trikudanathan et al reported a case of a schwannoma at the splenic flexure of the colon [ 30 ].…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…This mechanical property is required when puncturing a proximal colonic target lesion in the lower gastrointestinal tract. Akahoshi et al used a nitinol needle to puncture submucosal tumors in the descending colon [ 4 ]. The commonly used FNB needles are shown in Table 1 .…”
Section: Development Of Puncture Needlesmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, a standardized over-the-wire technique for colonic US using a flexible overtube has been reported with promising results: EUS-guided fine-needle aspiration (EUS-FNA) of lesions located proximal to the rectum was performed successfully in 13 patients with a diagnostic yield of 60% [ 23 ▪▪ ]. Another successful EUS-FNA sampling of a descending colon schwannoma was reported with a similar colonic intubation method [ 24 ].…”
Section: Endoscopic Ultrasound-guided Interventionsmentioning
confidence: 99%